Integrating Action Calculi and Description Logics - Drescher, C; Thielscher, M (Osnabrueck‚ Germany, 2007)
General action languages, like e.g. the Situation Calculus, use full classical logic to represent knowledge of actions and their effects in dynamic domains. Description Logics, on the other hand, have been developed to represent static knowledge with the help of decidable subsets of first-order logic. In this paper, we show how to use Description Logic as the basis for a decidable yet still expressive action formalism. To this end, we use ABoxes as decidable state descriptions in the basic Fluent Calculus. As a second contribution, we thus obtain an independent semantics – based on a general action formalism – for a recent method for ABox-Update.